"ProGRess" - Prokrastination reduzieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Prokrastination ressourcenstark und gesundheitsfördernd begegnen. - Schneider, Tamara; Klingsieck, Katrin B.

"ProGRess" - Ressourcen gegen Prokrastination aktivieren und Gesundheit fördern. - Schneider, Tamara; Klingsieck, Katrin B.

Dokumentation der Erhebungsinstrumente des Projekts WiGeMath - Schürmann, Mirko; Büdenbender-Kuklinski, C.; Lankeit, Elisa; Liebendörfer, Michael; Hochmuth, R.; Biehler, Rolf; Schaper, N.

Einblicke in explizite und implizite Erwartungen Lehrender an Studierendentexte. Textbasierte Interviews zu Zielen und Erträgen von fachsensiblem Peer-Textfeedback - Karsten, Andrea (Schreiblehrkonzepte an Hochschulen. Fallstudien und Reflexionen zum fachspezifischen Schreibenlehren und -lernen)

(Selbst-)Kritik und (Selbst-)Reflexion. Fragen stellen, Stimmen identifizieren, Referenzpunkte finden. - Karsten, Andrea (JoSch - Journal der Schreibwissenschaft)

TVA in the wild: Applying the theory of visual attention to game-like and less controlled experiments - Krüger, Alexander; Tünnermann, Jan; Stratmann, Lukas; Briese, Lucas; Dressler, Falko; Scharlau, Ingrid (Open Psychology)
As a formal theory, Bundesen’s theory of visual attention (TVA) enables the estimation of several theoretically meaningful parameters involved in attentional selection and visual encoding. As of yet, TVA has almost exclusively been used in restricted empirical scenarios such as whole and partial report and with strictly controlled stimulus material. We present a series of experiments in which we test whether the advantages of TVA can be exploited in more realistic scenarios with varying degree of stimulus control. This includes brief experimental sessions conducted on different mobile devices, computer games, and a driving simulator. Overall, six experiments demonstrate that the TVA parameters for processing capacity and attentional weight can be measured with sufficient precision in less controlled scenarios and that the results do not deviate strongly from typical laboratory results, although some systematic differences were found.

The time course of salience: not entirely caused by salience - Krüger, Alexander; Scharlau, Ingrid (Psychological Research)
Visual salience is a key component of attentional selection, the process that guards the scarce resources needed for conscious recognition and perception. In previous works, we proposed a measure of visual salience based on a formal theory of visual selection. However, the strength of visual salience depends on the time course as well as local physical contrasts. Evidence from multiple experimental designs in the literature suggests that the strength of salience rises initially and declines after approximately 150 ms. The present article amends the theory-based salience measure beyond local physical contrasts to the time course of salience. It does so through a first experiment which reveals that—contrary to expectations—salience is not reduced during the first 150 ms after onset. Instead, the overall visual processing capacity is severely reduced, which corresponds to a reduced processing speed of all stimuli in the visual field. A second experiment confirms this conclusion by replicating the result. We argue that the slower stimulus processing may have been overlooked previously because the attentional selection mechanism had not yet been modeled in studies on the time course of salience.

Advances in the application of a computational Theory of Visual Attention (TVA): Moving towards more naturalistic stimuli and game-like tasks - Tünnermann, Jan; Kristjansson, Arni; Petersen, Anders; Schubö, Anna; Scharlau, Ingrid (Open Psychology)
The theory of visual attention, “TVA”, is an influential and formal theory of attentional selection. It is widely applied in clinical assessment of attention and fundamental attention research. However, most TVA-based research is based on accuracy data from letter report experiments performed in controlled laboratory environments. While such basic approaches to questions regarding attentional selection are undoubtedly useful, recent technological advances have enabled the use of increasingly sophisticated experimental paradigms involving more realistic scenarios. Notably, these studies have in many cases resulted in different estimates of capacity limits than those found in studies using traditional TVA-based assessment. Here we review recent developments in TVA-based assessment of attention that goes beyond the use of letter report experiments and experiments performed in controlled laboratory environments. We show that TVA can be used with other tasks and new stimuli, that TVA-based parameter estimation can be embedded into complex scenarios, such as games that can be used to investigate particular problems regarding visual attention, and how TVA-based simulations of “visual foraging” can elucidate attentional control in more naturalistic tasks. We also discuss how these developments may inform future advances of TVA.

Kontaktlos lehren? - Reis, Oliver; Jenert, Tobias; Scharlau, Ingrid (Hochschule auf Abstand)

Wer bestimmt die Hochschullehre? - Reinmann, Gabi; Kreber, Carolin; Bremer, Helmut; Langemeyer, Ines; Scharlau, Ingrid (Hochschullehre im Spannungsfeld zwischen individueller und institutioneller Verantwortung: Tagungsband der 15. Jahrestagung der Gesellschaft für Hochschulforschung)

Jean Piaget als - was? - Scharlau, Ingrid (Interdisziplinarität als fachdidaktische Herausforderung: Psychologie im Schulfach Erziehungswissenschaft)

The digital home learning environment and its relation to children’s ICT self-efficacy - Bonanati, Sabrina; Buhl, Heike M. (Learning Environments Research)
With the rapid progress of technological development, self-efficacy in reference to digital devices (i.e., information and computer technology [ICT] self-efficacy) is an important driver that helps students to deal with technological problems and support their lifelong learning processes. Schools, peers, and home learning environments are important sources for the development of positive self-efficacy. Expanding on previous research, we investigated the associations between different aspects of the digital home learning environment and students’ ICT self-efficacy. The moderation effects of gender were also tested. A total of 651 children answered a questionnaire about different digital home learning environment dimensions and estimated their ICT self-efficacy using an adapted scale—Schwarzer and Jerusalem’s (1999) general self-efficacy scale. Using the structural equation modeling technique, a digital home learning environment containing six different qualities of parental support was investigated. Families’ cultural capital, parents’ attitudes toward the Internet, and shared Internet activities at home contributed positively to ICT self-efficacy. We observed small gender differences, with the moderation effect being nonsignificant. The results help researchers and practitioners to understand how different dimensions of the digital home learning environment support ICT self-efficacy. We will discuss how parents can enhance the home learning environment and how teachers can integrate this knowledge into formal education.
Keywords: Digital media use; Gender; Home learning environment; ICT self-efcacy; Motivation; Parental involvement

Latent Congruence Model to Investigate Similarity and Accuracy in Family Members' Perception: The Challenge of Cross-National and Cross-Informant Measurement (Non)Invariance - Tagliabue, Semira; Zambelli, Michela; Sorgente, Angela; Sommer, Sabrina; Hoellger, Christian; Buhl, Heike M.; Lanz, Margherita (Frontiers in Psychology)
Several methods are available to answer questions regarding similarity and accuracy, each of which has specific properties and limitations. This study focuses on the Latent Congruence Model (LCM; Cheung, 2009), because of its capacity to deal with cross-informant measurement invariance issues. Until now, no cross-national applications of LCM are present in the literature, perhaps because of the difficulty to deal with both cross-national and cross-informant measurement issues implied by those models. This study presents a step-by-step procedure to apply LCM to dyadic cross-national research designs controlling for both cross-national and cross-informant measurement invariance. An illustrative example on parent–child support exchanges in Italy and Germany is provided. Findings help to show the different possible scenarios of partial invariance, and a discussion related to how to deal with those scenarios is provided. Future perspectives in the study of parent–child similarity and accuracy in cross-national research will be discussed.
Keywords: latent congruence model; measurement invariance; similarity; accuracy; cross-national; cross-informant; parent-child relationship; support exchanges

Intergenerational Value Similarity and Subjective Well-Being - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Journal of Family Issues)
This investigation concentrates on the association of intergenerational value similarity and adult children’s and parents’subjective well-being, on the linkage between relationship quality and subjective well-being. Mediation effects of the relationship quality on the associations between value similarity and subjective well-being were focused. The sample consisted of 600 adult German children (53.8% women) and their parents. Dyadic correlations were constructed to determine the value similarity. In this study, the general value orientation and the family values were objects of research. We measured the subjective well-being with the Satisfaction with Life Scale and we used the Network of Relationships Inventory (NRI) to measure the relationship quality. Associations between subjective well-being and value similarity, and between subjective well-being and relationship quality, as well as mediation effects, were found. All effects depend on gender and perspective.
Keywords: adult child–parent dyads; relationship quality; life satisfaction; parent–child relationship; intergenerational stake hypothesis; mediation analyses

Zusammenhang zwischen der familiären Lebenssituation und Werteähnlichkeiten in der Eltern-Kind-Beziehung im Erwachsenenalter - Hoellger, Christian; Sommer, Sabrina; Buhl, Heike M. (Zeitschrift für Soziologie der Erziehung und Sozialisation)
Die Querschnittsuntersuchung beschäftigt sich mit der Fragestellung, ob in Zusammenhang mit der familiären Lebenssituation Erwachsener (Elternstatus und Beziehungsstatus) Unterschiede hinsichtlich der Werteähnlichkeit zwischen ihnen und ihren Eltern bestehen. Dabei wurde die Ähnlichkeit der individuellen Grundwerte nach Schwartz (1992) fokussiert. Die Werteähnlichkeit wurde mittels dyadischer Korrelationen bestimmt (Kenny & Winquist, 2001). Die Stichprobe bestand aus N= 1047 Dyaden. Dafür nahmen 600 erwachsene Kinder (53.8 % weiblich) mit ihren Eltern (542 Mütter und 505 Väter) teil. Das Alter der teilnehmenden Kinder lag zwischen 25 und 49 Jahren (M= 33.9, SD = 6.1). Die Ergebnisse dieser Studie zeigten, dass sich die Werteähnlichkeiten in Abhängigkeit von der familiären Lebenssituation unterschieden: Die Elternschaft der erwachsenen Kinder ging mit einer größeren Werteähnlichkeit in der Mutter-Kind-Dyade einher. Ebenso konnte eine größere Werteähnlichkeit zwischen verheirateten Söhnen und deren beiden Elternteilen beobachtet werden, verglichen mit den Söhnen, die Single oder in einer Partnerschaft waren. Die Werteähnlichkeit der Töchter zu ihren Eltern unterschied sich nicht in Abhängigkeit des Beziehungsstatus.

„Power-Posen“ – Fakten, frisierte Daten, Forschungslyrik? Eine Unterrichtsreihe zu Praktiken und Darstellungsformen psychologischer Forschung - Scharlau, Ingrid; Patrzek, Justine; Schreiber, Christine (Unterrichtsmaterial des Verbandes der Psychologielehrerinnen und –lehrer)
Keywords: Unterrichtsfach Psychologie

Kompetenzdiagnose in der Berufsbildung von Pflegelehrpersonen - Schürmann, Mirko; Bender, Elena; Grebe, Christian (Gruppe. Interaktion. Organisation. Zeitschrift für Angewandte Organisationspsychologie (GIO))
Zusammenfassung In diesem Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) wird das Instrument zur Diagnose pädagogischer Kompetenzen von Pflegelehrpersonen (PädKomPflege) vorgestellt. Die Berufsbildung in der Pflege ist durch sich verändernde inhaltliche und gesetzliche Anforderungen geprägt. Verschiedene landesspezifische rechtliche Vorgaben führen zu einem sehr heterogenen Bild von Qualifikationen und Kompetenzen der Pflegelehrpersonen. Die Anrechnung bereits erworbener Kompetenzen auf pflegepädagogische Studiengänge sowie die Kompetenzerfassung und -bilanzierung in Berufsbildungseinrichtungen spielt daher eine wichtige Rolle. Vor diesem Hintergrund wurde das Instrument PädKomPflege entwickelt und erprobt. Grundlage des Kompetenzmodells sind die Empfehlungen der Kultusministerkonferenz (2004) zu den Standards für die (allgemeine) Lehrerbildung sowie Expertenworkshops und -interviews mit PflegedidaktikerInnen. Die empirische Erprobung erfolgte an einer Stichprobe von 1096 Pflegelehrpersonen. Psychometrische Analysen auf Grundlage der klassischen Testtheorie sowie IRT-basierte Analysen führten zu einer Überarbeitung des Instruments, welches nun als zweisprachiges Online-Self-Assessmenttool (eng./deut.) vorliegt. Die Validierung der deutschsprachigen Version fand anhand von 545 TeilnehmerInnen im Jahr 2016 statt, sodass ein geprüftes Instrument mit 54 Items in den fünf Hauptskalen (Unterricht, Beurteilung, Beratung, Lernortkooperation sowie Organisations- und Schulentwicklung) und 18 Subskalen zur Verfügung steht. Sowohl klassische als auch probabilistische Testgütekriterien werden erfüllt. Die Skalen weisen hohe interne Konsistenzen auf ( α > 0,80) und sind überwiegend konstruktvalide. So lassen sich für 17 der 18 Subskalen ordinale Raschmodelle anpassen. Auf der Ebene der Hauptskalen können Partial Credit Modelle für alle Items von modellkonformen Subskalen einer Hauptskala angepasst werden. Das Instrument kann zur individuellen Kompetenzdiagnostik, zur Identifikation von Bildungsbedarfen in Schulen des Gesundheitswesens und im Kontext beruflicher Bildungsprozesse genutzt werden. In der Onlineversion erhalten Teilnehmende abschließend ein individuelles Kompetenzprofil mit möglichen Vergleichswerten. Das Tool kann begleitend zu Qualifizierungsprozessen als Monitoring-Instrument oder zur individuellen Kompetenzbilanzierung eingesetzt werden.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology; Developmental and Educational Psychology; Education; Social Psychology

Die Health Professionals Competence Scales (HePCoS) zur Kompetenzerfassung in den Gesundheitsfachberufen. Technical Report - Grebe, Christian; Schürmann, Mirko; Latteck, Änne-Dörte

Die Rolle von arbeitsplatzbezogener Flexibilisierung und die Betrachtung von individuellen Werten für Mitarbeitendenbindung in der Arbeitswelt 4.0 - Bender, Elena; Schürmann, Mirko; Poethke, Ute; Soyka, Chantal; Schaper, Niclas; Rowold, und Jens (Zeitschrift für Arbeits- und Organisationspsychologie A&O)
Zusammenfassung. In der Arbeit 4.0 ist durch neue Beschäftigungsmöglichkeiten für Mitarbeitende eine Langzeitbindung an ein Unternehmen seltener. Unternehmen reagieren mit flexibilisierten Arbeitsplätzen, um diesem Wunsch der Mitarbeitenden nachzukommen. Flexibilisierung reduziert die Absicht das Unternehmen zu verlassen. Dabei ist wichtig, räumliche und zeitliche Flexibilisierung zu differenzieren. Außerdem gewinnen individuelle Werte bezüglich Stabilität und Kontinuität an Bedeutung und können den Bindungswunsch stärken. Hauptziel dieser Untersuchung ist, anhand eines kontroll- und ressourcentheoretisch fundierten Rahmens in zwei aufeinander aufbauenden Studien ( N = 448, N = 202) die (potenziell unterschiedlich starken) Zusammenhänge von zeitlicher und räumlicher Flexibilisierung mit Mitarbeitendenbindung zu analysieren und zu prüfen, ob sich diese Zusammenhänge bestätigen lassen, wenn zusätzlich individuelle Werte in die Analyse einbezogen werden. Die Ergebnisse zeigen, dass zeitliche und räumliche Flexibilisierung unterschiedlich mit der Bleibeabsicht zusammenhängen. Während zeitliche Flexibilisierung positive Zusammenhänge zeigt, finden sich in Bezug auf räumliche Flexibilisierung keine Zusammenhänge. Werte bezüglich Stabilität und Kontinuität scheinen dabei nicht mit einer stärkeren Mitarbeitendenbindung zusammenzuhängen.
Keywords: Organizational Behavior and Human Resource Management; Applied Psychology